2022
DOI: 10.1155/2022/3907751
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Diagnostic Value of Neuroelectrophysiological Examination in Patients with Amyotrophic Lateral Sclerosis

Abstract: Objective. Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease with unknown causes involving upper and lower motor neurons. Our study aimed to explore the diagnostic value of neuroelectrophysiological examination in patients with amyotrophic lateral sclerosis. Methods. A total of 64 patients admitted to our hospital from January 2014 to December 2020 were selected as ALS group. Additionally, 64 normal healthy people in the same period were selected as the control group. Electrophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It has been reported that the amplitude of compound motor action potentials (CMAPs) evoked by peripheral nerve stimulation was reduced in patients with ALS, which positively correlated with the degree of muscle atrophy and weakness. 23 In addition, decreased CMAP amplitude in ALS is contemplated to reflect the loss of lower motor neurons. 24,25 In the present study, when the cutoff value of AH muscle potential evoked by peripheral nerve stimulation was set at 11.2 mV, ALS and CCM could be differentiated with relatively high accuracy (sensitivity and specificity of 87.5% and 85.7%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that the amplitude of compound motor action potentials (CMAPs) evoked by peripheral nerve stimulation was reduced in patients with ALS, which positively correlated with the degree of muscle atrophy and weakness. 23 In addition, decreased CMAP amplitude in ALS is contemplated to reflect the loss of lower motor neurons. 24,25 In the present study, when the cutoff value of AH muscle potential evoked by peripheral nerve stimulation was set at 11.2 mV, ALS and CCM could be differentiated with relatively high accuracy (sensitivity and specificity of 87.5% and 85.7%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the amplitude of CMAP and frequency of F waves, which were treated as characteristics of ALS, have been reported to be related to the severity of the disease, and it is not clear whether obvious abnormalities seem in the early stages. 23,29 However, patients with CCM who require surgical treatment often exhibit obvious limb motor deficits. Therefore, patients with ALS who require differentiation from such patients with CCM are unlikely to be in the early stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%